The gas metallicity gradient and the star formation activity of disc galaxies - Tissera, Patricia Beatriz (2016)
We study oxygen abundance profiles of the gaseous disc components in simulatedgalaxies in a hierarchical universe. We analyse the disc metallicity gradients in relationto the stellar masses and star formation rates of the simulated galaxies. We find a trendfor galaxies with low stellar masses to have steeper metallicity gradients than galaxieswith high stellar masses at z ∼ 0. We also detect that the gas-phase metallicityslopes and the specific star formation rate (sSFR) of our simulated disc galaxies areconsistent with recently reported observations at z ∼ 0. Simulated galaxies with highstellar masses reproduce the observed relationship at all analysed redshifts and have anincreasing contribution of discs with positive metallicity slopes with increasing redshift.Simulated galaxies with low stellar masses a have larger fraction of negative metallicitygradients with increasing redshift. Simulated galaxies with positive or very negativemetallicity slopes exhibit disturbed morphologies and/or have a close neighbour. Weanalyse the evolution of the slope of the oxygen profile and sSFR for a gas-rich galaxygalaxyencounter, finding that this kind of events could generate either positive andnegative gas-phase oxygen profiles depending on their state of evolution. Our resultssupport claims that the determination of reliable metallicity gradients as a function ofredshift is a key piece of information to understand galaxy formation and set constrainson the subgrid physics.